Economic theories of nonprofits and agricultural cooperatives compared: New perspectives for nonprofit scholars - Vladislav Valentinov; Constantine Iliopoulos (Nonprofit and Voluntary Sector Quarterly, 2013)
This article explores the cross-fertilization potential that exists between the economic theory of agricultural cooperatives and that of nonprofit organizations. A number of central ideas in the agricultural cooperative theory are shown to generate two novel insights pertaining to the nonprofit economics literature. First, as with agricultural cooperatives, nonprofit organizations can be conceptualized not only as firms but also as service agencies and stakeholder coalitions. Second, the demand-side economic justification of nonprofit organizations, like that of agricultural cooperatives, likely includes reasons other than market failure. The article concludes by calling for research on how nonprofit economics can inform the theory of agricultural cooperatives.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; nonprofit economics; agricultural cooperative; stakeholder; market failure